0034 Genetic Determinants of Cardiometabolic and Pulmonary Traits and Obstructive Sleep Apnea in the Hispanic Community Health Study/Study of Latinos. (25th May 2022) - Zhang, Yuan; Elgart, Michael; Kurniansya, Nuzulul; Spitzer, Brian; Wang, Heming; Shah, Neomi; Daviglus, Martha; Phylis, Zee; Cai, Jianwen; Gottlieb, Daniel; Cade, Brian; Redline, Susan; et al.
Abstract: Introduction: Obstructive sleep apnea (OSA) often co-occurs with other health outcomes. The respiratory event index (REI), often used to define OSA, is similarly correlated with several health phenotypes. Genetic data provide an opportunity to explain the nature of these associations. Methods: We used data from the Hispanic Community Healthy Study/Study of Latinos (HCHS/SOL) to estimate genetic correlations (i.e., the correlation between phenotypes that is due to genetic effects) between OSA severity as measured by the REI and 56 anthropometric, glycemic, cardiometabolic, and pulmonary traits. Genetically-correlated traits (>0.2 and p-value<0.05) were carried forward for additional analysis. Using summary statistics from published genome-wide association studies (GWAS), we constructed Polygenic Risk Scores (PRSs) representing the genetic basis of each correlated trait and OSA, and studied their associations with the genetically-correlated traits, REI and OSA. OSA was defined as REI5. When a PRS for a correlated-trait was associated (p-value<0.05) with REI/OSA or vice versa, we used GWAS summary statistics to test causal relationships using Mendelian Randomization (MR) analysis. We further estimated correlated-trait PRS associations with REI and OSA in subgroups of individuals with and without obesity (BMI>30). Results: The dataset included 11, 155 participants (mean age: 46.2 (SD =13.8) years; 41.1% males) from the baseline HCHS/SOL exam who underwent home sleep apnea testing. 30.65% had OSA. 22 traits were genetically correlated with REI. Without BMI adjustment, the PRSs of BMI, waist-to-hip ratio (WHR), diastolic blood pressure (DBP), pulse pressure (PP), HbA1c, triglycerides (TG), FEV1/FVC and insomnia were significantly associated with REI/OSA. The associations of WHR, DBP, PP, HbA1c and insomnia PRSs and REI/OSA remained in BMI adjusted analysis. In obesity-stratified analysis, PRS of BMI, WHR and DBP were associated with REI/OSA in individuals with obesity, while PRSs of FEV1/FVC, HbA1c, insomnia, PP, TG, and WHR were associated with REI/OSA in individuals without obesity. MR analysis identified robust causal effect of increased BMI on OSA, and suggestive causal effects of WHR, DBP, and PP on OSA. Conclusion: Our results support shared genetic basis of anthropometric traits, blood pressure traits, and insomnia with OSA, with potential differences in disease mechanisms in individuals with and without obesity. Support (If Any): Funding: R35HL135818, R21HL145425.